2019
DOI: 10.1021/acsphotonics.9b00894
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Reflection Colors from Metal–Insulator–Metal Cavity Structure Enabled by Thickness-Dependent Refractive Indices of Metal Thin Film

Abstract: Tunable structural colors have diverse applications ranging from displays and photovoltaics to surface decoration and art. A metal−insulator−metal (MIM) cavity structure formed by thin continuous layers has drawn great interest as a lithography-free and scalable optical structure to control light transmission and reflection at the surface of a material. However, the production of distinct reflection colors from the structure is challenging because the typical MIM cavity absorbs a narrow wavelength range and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 41 publications
5
48
0
Order By: Relevance
“…21,27 Thin lms may have refractive indices different from the bulkstate handbook data. In a previous report, 19 we showed that the refractive indices of Au and Ag lms deposited by thermal evaporation are strongly thickness dependent and coincide with the handbook data only for thicknesses over 40 nm. For a 10 nm-thick Au lm, the real part of the refractive index was comparable to its imaginary part at wavelengths longer than 600 nm, being highly lossy in this spectral range.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…21,27 Thin lms may have refractive indices different from the bulkstate handbook data. In a previous report, 19 we showed that the refractive indices of Au and Ag lms deposited by thermal evaporation are strongly thickness dependent and coincide with the handbook data only for thicknesses over 40 nm. For a 10 nm-thick Au lm, the real part of the refractive index was comparable to its imaginary part at wavelengths longer than 600 nm, being highly lossy in this spectral range.…”
Section: Resultssupporting
confidence: 85%
“…A Fabry-Perot (F-P) cavity comprising metalinsulator-metal (MIM) continuous layers is of signicant interest as a lithography-free planar structure for controlling the transmission, reection, and absorption of light. [19][20][21][22][23][24][25][26][27] In transmission mode where both metal layers are sufficiently thin (i.e., semitransparent), the cavity can selectively transmit a narrow frequency range of incident light, thus producing fairly vivid transmissive colors. The colors are tunable by varying the thickness of the insulator layer (i.e., the dielectric spacer).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the arrangement of the dipoles within a matrix does not affect or vary the specular reflection, yet the main contribution emerges from the dynamic polarizability of the arbitrary nanoparticles within the glassy medium as demonstrated by us [ 37,38,98 ] and adapted by other researchers. [ 99,100 ]…”
Section: Polarizonic Reflective Colorationmentioning
confidence: 99%
“…Consequently, the arrangement of the dipoles within a matrix does not affect or vary the specular reflection, yet the main contribution emerges from the dynamic polarizability of the arbitrary nanoparticles within the glassy medium as demonstrated by us [37,38,98] and adapted by other researchers. [99,100] The complex refractive index (RI) of the effective medium of the nanocomposite plays a crucial role in the optical behavior of the stacked system. In this regard, the imaginary part "k" is governed by absorption, thus engendering the well-known plasmonic colors.…”
Section: Introductionmentioning
confidence: 99%
“…Although [ 49 , 50 ] showed promising results, managing thin lossy metals requires special treatment. Recently, a broadband light absorber was constructed with absorption in the visible region by utilizing thermally evaporated Ag and Au layer [ 42 ] ( Figure 2 B), which exhibit refractive indices much different from the bulk-state value [ 51 ]. Nevertheless, the angle invariance was high, i.e., up to .…”
Section: Thin Films Color Filtersmentioning
confidence: 99%